A Chinese Family With Cerebral Cavernous Malformation Caused by a Frameshift Mutation of the CCM1 Gene: A Case Report and Review of the Literature - Liu, Wenyu; Liu, Ming; Lu, Di; Wang, Jiwei; Cao, Zexin; Liu, Xuchen; Feng, Zichao; Huang, Bin; Wang, Xinyu (Frontiers in Neurology, 2022)
Background Familial cerebral cavernous malformation (FCCM) is a vascular malformation disease closely linked to three identified genes: KRIT1/CCM1, MGC4607/CCM2 and PDCD10/CCM3. Over the past decade, a few cases of cerebral cavernous malformation (CCM) caused by different gene mutations have been reported in Chinese families. Herein, we introduce a Chinese family affected by FCCM due to a kind of KRIT1/CCM1 frameshift mutation. At the same time, a literature review was conducted to identify case reports of familial cerebral cavernous malformation. Case presentation The proband in the family in question demonstrated a series of clinical symptoms and features, including headache and bleeding. The proband was hospitalized for headache twice and, both times was examined under suspicion of CCM and received surgical treatment. Magnetic resonance imaging results showed that the proband had multiple intracranial vascular lesions, including on the brain, brainstem, and cerebellum. Genetic test results showed that the classic KRIT1 gene in the proband had a pathogenic mutation. The family members of the proband also showed typical cerebral cavernous malformation when considering clinical manifestations, magnetic resonance imaging findings and genetic test results. Conclusions We report a case of Chinese FCCM and its associated symptoms with CCM1-deletion mutations in China. Our findings deepen our understanding of CCM mutations and related phenotypes, the investigation results of this clinical experiment further show that the gene mutation form we reported plays an important role in human FCCM, and this trial investigation is beneficial for genetic counseling for CCM patients.